The Correlation Between Self Efficacy and Students’ Reading Comprehension - Jannatul Jannah, Wirda; Melliofatria (Journal of Applied Linguistics, 2025)
Reading is a crucial skill that must be mastered in learning English. This study aims to determine the correlation between self-efficacy and students' reading comprehension among sixth-semester students at the University of Pasir Pengaraian. The research employed a correlational design to investigate whether a relationship exists between self-efficacy and reading comprehension. Data were collected through a questionnaire and a multiple-choice test administered to 28 sixth-semester students. The analysis revealed a significant (2-tailed) value of 0.031, which is less than 0.05, indicating a correlation between self-efficacy and reading comprehension, though not a strong one. The results showed that self-efficacy in reading comprehension was generally high, with an average score of 72.86. Based on the questionnaire, 32% (9 students) fell into the very high category, while 68% (19 students) were in the high category. For the reading test results, 9 students (32%) were in the excellent category, 7 students (25%) in the good category, 8 students (29%) in the sufficient category, and 2 students (7%) each in the low and very low categories. From this data, the researchers concluded that students' reading comprehension falls into the good category, with an average score of 71.25. The correlation coefficient (rxy) was 0.408, which, according to the correlation index table, indicates a low correlation. Keywords : Self Efficacy, Reading Comprehension, Correlation